Meningkatkan Nilai Perusahaan: Dampak Kepemilikan Manajerial dan Pengungkapan CSR - Misheleiloen Misheleiloen (Journal of Accounting, Management, and Economics Research (JAMER), 2024)
The Influence of Managerial Ownership and Corporate Social Responsibility (CSR) Disclosure on Company Value (Empirical Study of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesian Stock Exchange for the 2017-2019 Period). To determine the influence of managerial ownership and Corporate Social Responsibility (CSR) disclosure on the value of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period. This research method uses multiple linear analysis methods. Managerial ownership has a significant negative influence on firm value partially. Disclosure of Corporate Social Responsibility (CSR) has a significant positive influence on company value partially. Managerial ownership and disclosure of Corporate Social Responsibility (CSR) have a significant positive influence simultaneously on company value. The managerial implications of this research explore the impact of managerial ownership and disclosure of Corporate Social Responsibility (CSR) on increasing company value. Managerial ownership plays an important role in aligning interests between management and shareholders, which in turn can motivate management to improve company performance. On the other hand, CSR disclosure not only builds a positive image of the company but also increases stakeholder trust and loyalty.